2022
DOI: 10.1021/acsnano.1c08913
|View full text |Cite|
|
Sign up to set email alerts
|

Intrinsic Radical Species Scavenging Activities of Tea Polyphenols Nanoparticles Block Pyroptosis in Endotoxin-Induced Sepsis

Abstract: Sepsis, a life-threating illness caused by deregulated host immune responses to infections, is characterized by overproduction of multiple reactive oxygen and nitrogen species (RONS) and excessive pyroptosis, leading to high mortality. However, there is still no approved specific molecular therapy to treat sepsis. Here we reported drug-free tea polyphenols nanoparticles (TPNs) with intrinsic broad-spectrum RONS scavenging and pyroptosis-blocking activities to treat endotoxin (LPS)-induced sepsis in mice. The R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 42 publications
0
71
0
Order By: Relevance
“…In addition, Chen et al reported that drug-free tea polyphenol nanoparticles (TPNs) exhibited excellent therapeutic efficacy in septic mouse models by scavenging reactive oxygen and nitrogen species and blocking pyroptosis. At the molecular level, TPNs can suppress the poreforming function of GSDMD by blocking its oligomerization, thus inhibiting pyroptosis (Chen et al, 2022). Furthermore, Wang et al identified an 8-hydroxyquinoline derivative named 7-[phenyl (pyridin-2-ylamino) methyl] quinolin-8-ol (8-ol, NSC84094), which specifically inhibits HMGB1-mediated caspase-11 signaling.…”
Section: Figurementioning
confidence: 99%
“…In addition, Chen et al reported that drug-free tea polyphenol nanoparticles (TPNs) exhibited excellent therapeutic efficacy in septic mouse models by scavenging reactive oxygen and nitrogen species and blocking pyroptosis. At the molecular level, TPNs can suppress the poreforming function of GSDMD by blocking its oligomerization, thus inhibiting pyroptosis (Chen et al, 2022). Furthermore, Wang et al identified an 8-hydroxyquinoline derivative named 7-[phenyl (pyridin-2-ylamino) methyl] quinolin-8-ol (8-ol, NSC84094), which specifically inhibits HMGB1-mediated caspase-11 signaling.…”
Section: Figurementioning
confidence: 99%
“…Additionally, TPNs block pyroptosis of NLRP3 inflammasome and non-inflammasome activators in a dose-dependent manner. This suggests that TPNs have the potential to treat sepsis and deserve more systematic preclinical studies for clinical translation [ 8 ].…”
Section: Disease Therapeutic Drug Candidate-based On Gsdmd Inhibitionmentioning
confidence: 99%
“…In sepsis, the dysregulation of the body's inflammatory response culminates in a major inflammatory outbreak that is fatal. Recent studies have identified that an inflammatory cell death process known as pyroptosis, a programmed cell death mechanism commonly found in pathogenic infection states, plays an important role in sepsis [ 8 ]. During pyroptosis, immune cells release pro-inflammatory cytokines to recruit other immune cells to fight infection, enhance the host's defense response, and facilitate the elimination of invading pathogens [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…37 Moreover, the abundant phenolic structures endow them with the abilities to relieve the pressure of oxidative stress by donating hydrogen atoms to stabilize the active ROS. [38][39][40][41][42][43] However, the instabilities, short cycle time and potential penetration toxicity limit the further therapeutic applications of these naturally occurring bio-active molecules due to these features of small molecules. 29,30,38 Therefore, various strategies have been designed to solve the above problems and promote the development of these functional materials.…”
Section: Introductionmentioning
confidence: 99%